Analysis of pollen-specific alternative splicing in Arabidopsis thaliana via semi-quantitative PCR - Estrada,April D; Freese,Nowlan H; Blakley,Ivory C; Loraine,Ann E (PeerJ PrePrints, 2015)
Alternative splicing enables a single gene to produce multiple mRNA isoforms by varying splice site selection. In animals, alternative splicing of mRNA isoforms between cell types is widespread and supports cellular differentiation. In plants, at least 20% of multi-exon genes are alternatively spliced, but the extent and significance of tissue-specific splicing is less well understood, partly because it is difficult to isolate cells of a single type. Pollen is a useful model system to study tissue-specific splicing in higher plants because pollen grains contain only two cell types and can be collected in large amounts without damaging cells. Previously, we identified pollen-specific splicing patterns by comparing RNA-Seq data from Arabidopsis pollen and leaves. Here, we used semi-quantitative PCR to validate pollen-specific splicing patterns among genes where RNA-Seq data analysis indicated splicing was most different between pollen and leaves. PCR testing confirmed eight of nine alternative splicing patterns, and results from the ninth were inconclusive. In four genes, alternative transcriptional start sites coincided with alternative splicing. This study highlights the value of the low-cost PCR assay as a method of validating RNA-Seq results.
Keywords: RNA-Seq; Integrated Genome Browser; Arabidopsis thaliana; Pollen; Alternative Splicing; Semi-Quantitative PCR